Determination of Macroelements and Microelements in Flos Sophorae by ICP-OES with Microwave Digestion - Ma, Suying; Xia Lv, Hai; Shang, Xiaojun (Asian Journal of Chemistry, 2012)
The contents of macroelements and microelements (Na, K, Ca, P, Mg, Mn, Fe, Zn, As, Cu, Se, Cr, Cd, Ni and Pb) in flos sophorae were studied by ICP-OES with microwave digestion. The best operation conditions of microwave digestion and ICP-OES were optimized. The results indicated that there were high contents of K, P, Ca, Mg, Na, Fe elements in flos sophorae and the sequence of metal elements contents is as follows P > Na > K > Ca > Mg > Fe > Zn > Mn > Cu > As > Cr > Se > Cd, while Ni and Pb elements were not detected. The ICP-OES with microwave digestion method is simple and accurate enough for determination of macroelements and microelements in flos sophorae.